Telecommunication Networks in Germany — Expanding with a Public Company - Cordelius Ilgmann; André Störr (Wirtschaftsdienst)
Abstract The broadband network in Germany still meets current demand. However, the quality of the existing infrastructure offers little incentive for private investors to adapt their infrastructure to future needs. Hence, the expansion of fibre optic lines is progressing too slowly. Government subsidy programmes create additional problems. A strategic reset is needed as the future will be a convergent system of fibre optic lines and mobile networks. The authors propose that the restructuring of the telecommunications infrastructure be entrusted to a state-owned infrastructure company. It should plan and construct nationwide fibre optic and mobile networks in a coordinated manner, based on a coherent analysis of demand and supply. Competition will then take place at the level of network operation and the provision of communication services.